Using fall‐seeded cover crop mixtures to enhance agroecosystem services: A review. Issue 2 (10th May 2021) - Lavergne, Stéphanie; Vanasse, Anne; Thivierge, Marie‐Noëlle; Halde, Caroline
Abstract: The intensification of agriculture has resulted in the loss of species diversity in agroecosystems. Crop diversification not only improves ecosystem functions but increases agroecosystem resilience to climate change. Cover crops (CC) are used in the crop rotation to increase plant diversity and provide continuous living roots and soil cover. Previous studies have focused mainly on pure stands of CC and on binary mixtures. In recent years, there has been a growing interest in multispecies mixtures (>2 species). Here, we review reports from the literature to document the effectiveness of fall‐seeded CC mixtures to provide agroecosystem services such as weed suppression, N cycling, soil organic C storage, and crop productivity. We cover both organic and conventional field crop systems in North America and Europe. We found, for both systems, that fall‐seeded CC mixtures increased many agroecosystem services compared with a control without CC; however, they had inconsistent effects in comparison with a pure stand. The capacity of mixtures to enhance a given agroecosystem service was found to be dependent on the species functional group. Legume‐based mixtures increased soil N and C contents along with crop yield, whereas nonlegume mixtures improved N recycling and weed suppression. Differences in the functional groups within CC mixtures could lead to trade‐offs among agroecosystem services. Future research should focus on what drives species‐specific contributions to productivity and other ecosystem services when CC are seeded in mixtures. More long‐term research is needed to provide better insights into the stability of the ecosystem services provided by CC mixtures. Core Ideas: Agroecosystem services relate more to species functional groups than to species richness. Cover crop mixtures provide similar services in organic and conventional systems. Legume‐based mixtures are preferred for N supply and yield services. Nonlegume mixtures are preferred for weed suppression and N cycling.